Bio‐Organic Chiral Nematic Materials with Adaptive Light Emission and On‐Demand Handedness. Issue 38 (31st July 2021) - Kang, Saewon; Li, Yingying; Bukharina, Daria; Kim, Minkyu; Lee, Hansol; Buxton, Madeline L.; Han, Moon Jong; Nepal, Dhriti; Bunning, Timothy J.; Tsukruk, Vladimir V.
Abstract: Real‐time active control of the handedness of circularly polarized light emission requires sophisticated manufacturing and structural reconfigurations of inorganic optical components that can rarely be achieved in traditional passive optical structures. Here, robust and flexible emissive optically‐doped biophotonic materials that facilitate the dynamic optical activity are reported. These optically active bio‐enabled materials with a chiral nematic‐like organization of cellulose nanocrystals with intercalated organic dye generated strong circularly polarized photoluminescence with a high asymmetric factor. Reversible phase‐shifting of the photochromic molecules intercalated into chiral nematic organization enables alternating circularly polarized light emission with on‐demand handedness. Real‐time alternating handedness can be triggered by either remote light illumination or changes in the acidic environment. This unique dynamic chiro‐optical behavior presents an efficient way to design emissive bio‐derived materials for dynamic programmable active photonic materials for optical communication, optical coding, visual protection, and visual adaptation. Abstract : A robust and flexible chiral emissive bio‐nanocomposite with chiral nematic‐like organization that mimics the biological photonic mesostructure observed in nature are demonstrated. Small molecules built in chiral mesostructure are assembled along helical arrangement, allowing the generation of strong active circularly polarized light emission. Real‐time phase transition of the molecules integrated into the biophotonic structure enables highly asymmetric circularly polarized light emission with on‐demand handedness.